Distributed .NET with Microsoft Orleans : build robust and highly scalable distributed applications without worrying about complex programming patterns /: build robust and highly scalable distributed applications without worrying about complex programming patterns. (2022) - Muthiyalu, Bhupesh Guptha; Kunani, Suneel Kumar
No abstract available